Hyperreality of #BlackLivesMatter movement on social media - Pradhana, Ghozian Aulia; Syaifa Tania (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to reveal how hyperreality is reflected in using the #BlackLivesMatter hashtag on social media. The death of an African-American, George Floyd, that involved white police, has sparked outrage and demonstrations in many U.S. states. Issues pertaining to racism sparked in relation to the event, and many people protested demanding justice. The demand for justice then went into a wave of massive global protests both in offline and online realities—the #BlackLivesMatter hashtag was widely used on social media when protests were held. The #BlackLivesMatter hashtag even became a trending topic on several social media platforms, as if everyone was concerned about the issue and aiming for the same purpose. However, we might find several posts that neither reflected nor were related to the case. Some social media users put the hashtag even though their content substance was not related. This phenomenon then led to a condition of hyperreality in questioning reality from a simulation of reality. The method used in this study is content analysis which measures the sentiment of comments on Twitter and Instagram. The study found that social networking sites mobilised online movements even though they were not directly related to the #BlackLivesMatter movement. On the other hand, hashtag activism reduced the true meaning of the social movement. Therefore, the hyperreality in #BlackLivesMatter could not be seen any longer as a form of massive protests demanding justice and ending violence, but merely to gain more digital presence on social media.